MEWIRAUSAHAKAN BIROKRASI - Hakim, Lukmanul (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2013)
Abstrak A context about bureaucracy of entrepreneurship prominently become a discussion of Indonesian bureaucracy during various crisis that wave government base and economic. The fairness of information and democratic mainstream that coloured